FEATURES DECRYPTING THE ORGANIZATIONAL CULTURE OF A COMMERCIAL ORGANIZATION - Nadezhda Petrovna Litvinova (Science and Innovation Center Publishing House, 2020)
The study of organizational culture is a relatively new direction in management, which was developed when it became clear that the commercial success of companies is predetermined by their high organizational culture. But the problem of deciphering the organizational culture of a particular enterprise is the main one that modern researchers in this field are working on. One of the effective tools to solve this problem is the method of “clinical examination”, called by E. Shane “iterative clinical interview”. The article considers the experience of conducting such research on the example of a specific commercial organization.